Mechanochemically activated microscale zero-valent iron with carboxymethylcellulose for efficient sequestration of phosphate in aqueous solution. Issue 1 (February 2023) - Shen, Wenjuan; Liu, Zhan; Quan, Fengjiao; Zhang, Xu; Peng, Xing; Wang, Xiaobing; Wang, Wenqing; Huang, Lan; Zhang, Shunxi; Li, Jianfen; Mei, Yunjun
Abstract: This study modified microscale zero valent iron (mZVI) using hydrophilic sodium carboxymethyl cellulose (CMC) via mechanical ball milling method, which was donated as CMC-mZVI, and compared the phosphate removal performance of mZVI and CMC-mZVI. Characterization results of X-ray powder diffractometer (XRD), Fourier transform infrared spectroscopy (FTIR), EDS-mapping images of CMC-mZVI demonstrated that the dominant crystalline structure of mZVI did not alter significantly after the ball-milling process and CMC could be adsorbed on the surface of mZVI. Further phosphate (PO4 3- ) removal experimental results revealed that the PO4 3- removal percentage of CMC-mZVI within 360 min was 99.99 %, which was much higher than that of mZVI (75.23 %). Subsequently, this study analyzed the concentration of ferrous ions and total iron ions dissolved by mZVI and CMC-mZVI, compared the high resolution X-ray photoelectron spectroscopy (HR-XPS) of mZVI and CMC-mZVI before and after the phosphate removal, and characterized the affinity of CMC-mZVI (or mZVI) to water by testing the static contact angle between CMC-mZVI (or mZVI) and water. The above results suggested that the existence of CMC on the surface of mZVI could promote the hydrophilic property of mZVI, resulting the enhancement of ferrous ions and total iron ions dissolution by 8 and 8.78 times than that of mZVI, and the rapid co-precipitation of phosphate. This study provided an environmentally friendly and effective method to improve the reactivity of commercial mZVI powder, and contributed to the wide application of mZVI technology in the field of environmental remediation. Graphical Abstract: ga1 Highlights: CMC-mZVI was prepared via ball milling method. CMC modification promoted PO4 3- removal percentage of mZVI from 75.23 % to 99.99 %. CMC endowed mZVI with high hydrophilicity.